Multi-Factor Authentication Model with Light Weight Encryption for Cloud IoT Systems - Dr. S. Ashok Kumar; R. Latha (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The quick development of Cloud-IoT systems has enabled large-scale automation, universal sensing, and intelligent decision-making across various application domains, including smart cities, industrial IoT, healthcare and transportation. However, the integration of resource-constrained IoT devices with cloud platforms familiarizes significant security encounters, predominantly in authentication and in data protection. Traditional cryptographic and authentication structures look to be computationally very intensive which makes them inappropriate for low-power IoT architectures. This research recommends a robust and energy effective security framework that integrates the Multi-Factor Authentication (MFA) with the lightweight encryption to ensure secure device access, user authentication and data confidentiality in Cloud-IoT environments. The proposed MFA model incorporates possession-based, knowledge-based and behavioral factors thereby minimalizing the threat of credential compromise and the unauthorized access. Lightweight encryption algorithms such as SPECK and PRESENT are labouring to produce cryptographically secure authentication tokens and protect announcement without overloading the constrained devices. Investigational evaluations validate better-quality resistance to replay, impersonation and brute-force attacks while achieving low computational overhead. The mixture of MFA and lightweight cryptography efficiently supports trust, enhances system resilience, and provides a scalable security architecture suitable for next-generation IoT deployments.